MATHEMATICA notebook for computing tetrahedral finite element shape functions and matrices for the Helmholtz equation - Franco, MAR; Passaro, A.; Machado, J. M. (Institute of Electrical and Electronics Engineers (IEEE), 1998)
A MATHEMATICA notebook to compute the elements of the matrices which arise in the solution of the Helmholtz equation by the finite element method (nodal approximation) for tetrahedral elements of any approximation order is presented. The results of the notebook enable a fast computational implementation of finite element codes for high order simplex 3D elements reducing the overheads due to implementation and test of the complex mathematical expressions obtained from the analytical integrations. These matrices can be used in a large number of applications related to physical phenomena described by the Poisson, Laplace and Schrodinger equations with anisotropic physical properties.
Keywords: Helmholtz equations; finite element methods; anisotropic media; software tools